Effectiveness of Digital Intervention on Improving Mental Health Literacy and Health Service Utilization - Akmal Hidayat; Nur Aeni Rahman; Zahrotul Ainil Mahfudhah Umar; Nurfaisa Riono; Abd Majid (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
The purpose of this study is to assess how well the "MindWell" information system facilitates the assessment and tracking of users' mental health. "MindWell" is an online resource created to give consumers quick and simple access to mental health assessments, educational materials, and expert advice. Using cutting-edge web technology, this system offers real-time screening services, ensures user data confidentiality and privacy, and includes features like mental health education, support service referrals, and monitoring. The system's capacity to offer pertinent information and assist users in understanding their mental health disorders was examined, along with input from beta users and a series of trial runs. The findings demonstrated that "MindWell" was successful in raising users' awareness of mental health issues, assisting in the early detection of mental health issues, and giving them access to helpful resources. It is envisaged that the deployment of this system will aid in the pursuit of more widespread and long-lasting improvements in mental health.